Hukum Menghimpun dan Mengelola Dana Sosial Bagi Filantrofi Islam - Roby Abdullah Mustika; Abd Wahab Abd Muhaimin; Umi Khusnul Khotimah (STAI Al-Mas'udiyah, 2025)
This research is motivated by the collection and management of Islamic Philanthropy funds that are different from what has been determined both in sharia economic law and in the laws and regulations in force in Indonesia. This is an important instrument in the social and economic development of the people, especially through the mechanism of collecting and managing social funds such as zakat, infaq, sadaqah, and waqf. This study aims to analyze the perspective of Islamic law on the practice of collecting and managing social funds, whether by individuals, institutions or the state. In this context, the principles of fiqh muamalah and maqashid al-syariah become the normative basis in ensuring that the management of social funds is trustworthy, transparent, and right on target. The research method used is a library research with a normative-theological approach. The results of the study show that Islamic law encourages structured and professional management of social funds, which can be done through official Islamic philanthropic institutions that have public accountability. The law also provides provisions regarding the conditions for the validity of managers, fund distribution mechanisms, and prohibitions against misappropriation of social funds. In the modern era, the importance of sharia regulation and strengthening philanthropic governance is key in increasing public trust and participation. In conclusion, Islamic law provides a clear and flexible framework for the management of social funds, while emphasizing the values of justice, efficiency, and sustainability for the benefit of the people.